Persistent post-surgical pain: Prevalence, risk factors and pain mechanisms - Johansen, Aslak (UiT The Arctic University of Norway, 2015)
The papers of this thesis are not available in Munin: Paper I. Persistent postsurgical pain in a general population: Prevalence and predictors in the Tromsø study. Johansen A, Romundstad L, Nielsen CN, Schirmer H, Stubhaug A. Available in PAIN®, vol. 153, issue 7, 2012, pp. 1390–1396 Paper II. Persistent post-surgical pain and experimental pain sensitivity in the Tromsø study: Comorbid pain matters. Johansen A, Schirmer H, Stubhaug A, Nielsen CS. Available in PAIN®, vol. 155, issue 2, 2014, pp. 341-348 Paper III. Persistent post-surgical pain and signs of nerve injury. The Tromsø Study. (Manuscript). Persistent pain is reported to be a frequent complication from surgery. Among the proposed risk factors are perioperative nerve injury and individual differences in pain sensitivity. The 6th Tromsø Study, a cross-sectional survey and medical examination, provided questionnaire data on persistent pain in general and persistent pain following surgery in particular. Participants performed tests of sensitivity to experimental pain stimuli. A sample of participants who had performed surgery 3-36 months before the survey, were re-assessed with questionnaires and quantitative assessments of sensory function 15-32 months after Tromsø 6. In accordance with previous research, we found that persistent pain after surgery was common. Moderate or severe pain in the area of surgery 3-36 months after the procedure was reported by 18.3 %. Most cases were coexistent with other chronic pain. Only in a small minority of cases did the patients themselves attribute persistent pain to surgery alone. In a general surgical sample, we could not identify specific associations between persistent post-surgical pain and sensitivity to experimental pain stimuli when comorbid pain was adjusted for. Persistent post-surgical pain was strongly associated with self-reported sensory disturbances, indicating possible nerve injury as a contributing factor. Sensory aberrations were confirmed with sensory testing in a majority of individuals with ...